Right of appreciation in civil evidence comparative study - ABDULLAH MHMOOD ALFAIDHI, AWAN (International Journal of Psychosocial Rehabilitation, 2020)
The right of the calendar is one of the legal means that have been found to protect rights from conflict or abuse. They are closely related to the right and are accompanied by existence and infallibility. The purpose of their legislation is to seek justice and to protect the rights of individuals from loss. It is impossible for the judge to determine the true value of the thing, and then he can direct the oath. But it has to determine its true value. And not the value of the plaintiff; the judge determines in this case the maximum value of the plaintiff's right, and this value of the plaintiff does not abide by the judge; because it is a complementary right, he can rule less than that value or more according to his authority and Maitra him. It provides real evidence relative to the value of the thing; it remains to strengthen this evidence with a legal right complementary to the right of the calendar addressed to the plaintiff, which calls for the recovery of the object and the impossibility of the response; its goal is to assess the value of the thing and show the right to protect rights from loss and non-aggression.